Demystification of readiness, security, and technological enhancements in the adoption of a cashless economy - Heru Susanto; Noor Tamtini; Fahmi Ibrahim; Alifya Kayla Shafa Susanto; Desi Setiana; Leu Fang Yie (Economies, 2024)
The adoption of a cashless economy was accelerated globally by the devastating impact of the COVID-19 pandemic. Brunei Darussalam was not excluded from this trend, as pandemic-related restrictions were implemented to ensure the safety of its population. In light of the COVID-19 crisis, this research paper examines the factors influencing the readiness and acceptance of a cashless economy among working society in Brunei Darussalam. The integrated concepts of the Technology Acceptance Model (TAM) and Technology Readiness Index (TRI) are applied to examine perceptions impacting their acceptance and readiness to continue adopting a cashless economy. The methodology includes a literature review and the use of secondary data from government reports and industry publications. A quantitative approach is employed, utilizing an online survey to collect non-probability samples from 212respondents. The main instruments used in the survey are structured questionnaires. The study's findings show that factors such as the assessment of payment modes, technological development, digital literacy, knowledge, regulatory policies, and security concerns significantly affect working society's perceptions, readiness, and acceptance of a cashless economy. These results provide insights for policymakers and stakeholders on the key factors influencing continued cashlessness adoption and shaping societal behavior towards cashless payments.
Keywords: 330; adoption; cashless payments; perceptions; technology readiness index; technology acceptance model; COVID-19 pandemic; working society; cashless economy